Automatic Identification of the Main Ionospheric Trough in Total Electron Content Images. Issue 6 (27th June 2022) - Starr, Gregory; Mrak, Sebastijan; Nishimura, Yukitoshi; Hirsch, Michael; Ishwar, Prakash; Semeter, Joshua
Abstract: The main ionospheric trough (MIT) is a salient density feature in the mid‐latitude ionosphere and characterizing its structure is important for understanding Global Positioning System and HF signal propagation, and identifying geospace phenomena such as the plasmapause boundary layer. While a number of previous studies have statistically investigated the properties of the MIT utilizing low‐altitude satellite observations, they have been limited to latitudinal cross sections, and have not considered the inherent two‐dimensional structure of the MIT. In this work, we develop a regularized inversion method for identifying the two dimensional structure of the MIT in Total Electron Content maps. Because no ground truth labels exist for the MIT, we extensively characterize the behavior of the algorithm by comparing it to the method developed by Aa, Zou, et al. (2020, doi:https://doi.org/10.1029/2019JA027583 ). We show that statistics computed on the resulting labels are robust to our choice of algorithm parameters and that we are able to match the results of Aa, Zou, et al. (2020, doi:https://doi.org/10.1029/2019JA027583 ) with a particular selection of the parameters. In addition to enabling fundamentally different studies, our MIT labels are able to provide statistical MIT properties with higher resolution. Code to reproduce our data set is provided in a GitHub repository: https://github.com/gregstarr/trough . Plain Language Summary: The Earth's ionized outer atmosphere (the ionosphere) serves as the interface between our atmosphere and the near space environment. Signals from Global Positioning System satellites contain information about the total integrated plasma density (referred to as "Total Electron Content, " (TEC)) between a given satellite and a given ground receiver. Measurements of TEC from large networks of ground receivers allow us to construct global images of the ionosphere, and thus study its variations in space and time. This paper uses such ionospheric images over a 20 year period to investigate a large‐scale coherent density depletion in the ionosphere known as the "mid‐latitude ionospheric trough" (MIT). In this work we have identified and labeled MIT regions in each images using computer vision techniques, and stored the results in a new image database. Using this "labeled data, " we can gain insight into the average location, morphology, and occurrence rates of the MIT, an examine this phenomenon varies with season, time of day, geomagnetic activity, and other correlated parameters. Key Points: A method for identifying the main ionospheric trough (MIT) in global Total Electron Content images is developed and validated Statistics extracted from a 10‐year data set are found to be in good agreement with a SWARM‐derived satellite model Our technique enables statistical analyzes of two‐dimensional (lat, lon) MIT properties with high resolution